\def\problem#1{\goodbreak\bigskip\noindent{\bf #1)}\smallskip\penalty500} \newfam\rsfs \newfam\bbold \def\scr#1{{\fam\rsfs #1}} \def\bb#1{{\fam\bbold #1}} \let\oldcal\cal \def\cal#1{{\oldcal #1}} \font\rsfsten=rsfs10 \font\rsfssev=rsfs7 \font\rsfsfiv=rsfs5 \textfont\rsfs=\rsfsten \scriptfont\rsfs=\rsfssev \scriptscriptfont\rsfs=\rsfsfiv \font\bbten=msbm10 \font\bbsev=msbm7 \font\bbfiv=msbm5 \textfont\bbold=\bbten \scriptfont\bbold=\bbsev \scriptscriptfont\bbold=\bbfiv \def\E{\bb E} \def\P{\bb P} \newcount\qnum \def\fr#1#2{{#1\over #2}} \def\var{\mathop{\rm var}\nolimits} \def\cov{\mathop{\rm cov}\nolimits} \def\dd#1#2{\fr{\partial #1}{\partial #2}} \problem{1} \noindent{\bf (a)} $$\E(Z) = \pmatrix{1\cr0}\qquad \var(Z) = \pmatrix{2&c\cr c&4}$$ \noindent{\bf (b)} Covariance is a bilinear function, and $\var (kX) = \cov(kX,kX) = k^2\var X.$ Also, $\cov(c, X) = 0,$ if $c$ is a constant, regardless of $X.$ (because $\cov(c, X) = \E(cX) - \E(c)\E(X) = c\E(X) - c\E(X) = 0.$) With linearity, this means $\cov(X+c, Y+b) = \cov(X, Y).$ $$\rho(2X-1, 5-Y) = {\cov(2X-1, 5-Y)\over\sqrt{\var(2X-1)}\sqrt{\var(5-Y)}} = {\cov(2X, -Y)\over\sqrt{\var(2X)}\sqrt{\var(-Y)}} = $$$$ {-2\cov(X, Y)\over2\sqrt{\var(X)}\sqrt{\var(Y)}} = -{.5\over\sqrt{2}\sqrt{4}} = -{\sqrt2\over8}.$$ \noindent{\bf (c)} $X$ and $Y$ are not necessarily independent from each other, although independence would give a covariance of 0 ($p_XY(x,y) = p_X(x)p_Y(y) \to \E(XY) = \E(X)\E(Y).$) Let $W \sim \cal N(0, 1),$ and $Z \sim 2\cal B(.5) - 1$ (i.e. it has a .5 probability of being -1 or 1). $X := \sqrt2 W + 1$ and $Y := 2ZW.$ These are strictly dependent because $Y = \sqrt2Z(X-1),$ so $Y$ has conditional distribution $\sqrt2(x-1)(2\cal B(.5) - 1),$ which is clearly not equal to its normal distribution (which can be fairly easily verified by symmetry of $W$). However, they have covariance 0: $$\E(XY) - \E X\E Y = \E((\sqrt2 W + 1)2ZW) - \E(\sqrt 2 W + 1)\E(2ZW) $$$$ = \E(2\sqrt2 ZW^2) - \E(\sqrt 2 W)\E(2ZW) = 0 - 0\E(2ZW) = 0. $$ % wikipedia says no \problem{2} \noindent{\bf (a)} \def\idd#1#2{\dd{#1}{#2}^{-1}} $Y_1 = 2X_2$ and $Y_2 = X_1 - X_2$ give us $X_2 = Y_1/2$ and $X_1 = Y_2 + Y_1/2.$ This lets us compute Jacobian $$J = \left|\matrix{\idd{x_1}{y_1} &\idd{x_1}{y_2}\cr \idd{x_2}{y_1} &\idd{x_2}{y_2}}\right| = \left|\matrix{2&1\cr2&0}\right| = -2.$$ $$g(y_1, y_2) = \left\{\vcenter{\halign{\strut$#$,&\quad$#$\cr |J|2e^{-(y_2+y_1/2)}e^{-y_1/2} & 0 < y_2+y_1/2 < y_1/2\cr 0 & {\rm elsewhere}\cr }}\right.$$ $y_2+y_1/2 < y_1/2 \to y_2 < 0 \to -y_2 > 0.$ And $0 < y_2 + y_1/2 \to y_1 > -2y_2 > 0.$ $$ = \left\{\vcenter{\halign{\strut$#$,&\quad$#$\cr 4e^{-y_2}e^{-y_1}&y_1 > -2y_2 > 0\cr 0&{\rm elsewhere}\cr }}\right.$$ \noindent{\bf (b)} $$g(y_1) = \int_{-\infty}^\infty g(y_1,y_2)dy_2 = \bb I(y_1>0)\int_{-y_1/2}^0 4e^{-y_1}e^{-y_2} dy_2 = \bb I(y_1>0)4e^{-y_1}(1-e^{y_1/2}).$$ $$g(y_2) = \int_{-\infty}^\infty g(y_1,y_2)dy_1 = \bb I(y_2<0)\int_{-2y_2}^\infty 4e^{-y_1}e^{-y_2} dy_1 = \bb I(y_2<0)4e^{-y_2}(-e^{2y_2}) .$$ \noindent{\bf (c)} They are independent iff $g(y_1,y_2) \bb I(y_1 > -2y_2 > 0)e^{-y_1-y_2} = g(y_1)g(y_2) = \bb I(y_1 > 0)\bb I(y_2 < 0) h(x),$ where $h(x)$ is the strictly non-zero product of exponents that would result, showing that they are dependent (if $y_1 = -y_2 = 1,$ the right indicators are satisfied but not the left indicator, and since $h(x)$ is non-zero, we see a contradiction.) \problem{3} \noindent{\bf (a)} We start determining the mgf from the pdf of $X,$ $p_X(x) = \fr1{\sqrt{2\pi}}e^{-\fr12x^2}.$ $$\E(e^{tX}) = \int_{-\infty}^\infty e^{tx}\fr1{\sqrt{2\pi}}e^{-\fr12x^2} dx = \fr1{\sqrt{2\pi}} \int_{-\infty}^\infty e^{tx-\fr12x^2} dx = $$$$ \fr1{\sqrt{2\pi}} \int_{-\infty}^\infty e^{tx-\fr12x^2-\fr12t^2 + \fr12t^2} dx = e^{\fr12t^2} \int_{-\infty}^\infty \fr1{\sqrt{2\pi}}e^{-\fr12(x-t)^2} dx = e^{\fr12t^2}, $$ by the final integrand being a normal pdf and therefore integrating to 1. \noindent{\bf (b)} $$M_Y(t) = \E(e^{t(aX+b)}) = \E(e^{bt}e^{atX}) = e^{bt}\E(e^{atX}) = e^{bt}M_X(at) = e^{bt}e^{\fr12(at)^2}.$$ \noindent{\bf (c)} Theorem 1.9.2 states that two probability distribution functions are alike if and only if their moment generating functions are equal in some vicinity of zero. The mgf of $Y$ corresponds to $\cal N(b, a^2),$ which has the following mgf (by computation from its pdf definition): $$\int_{-\infty}^\infty e^{tx}\fr1{a\sqrt{2\pi}}e^{-(x-b)^2\over 2a^2} dx = \fr1{a\sqrt{2\pi}}\int_{-\infty}^\infty e^{2a^2tx - x^2 + 2bx - b^2\over 2a^2} dx =$$$$ \fr1{a\sqrt{2\pi}}\int_{-\infty}^\infty e^{-(b+a^2t)^2 + 2(a^2t+b)x - x^2 - b^2 + (b+a^2t)^2\over 2a^2} dx = e^{(b+a^2t)^2-b^2\over 2a^2}\int_{-\infty}^\infty \fr1{a\sqrt{2\pi}}e^{-(b+a^2t+x)^2 \over 2a^2} dx = e^{bt}e^{(at)^2\over2}, $$ proving $Y \sim \cal N(b, a^2),$ because this function is convergent everywhere, and reusing the fact that the final integrand is a normal pdf, so it must integrate to 1. \bye